Meningkatkan Kemampuan Bahasa Lisan Anak Melalui Metode Bercerita Dengan Media Audio Visual di Tk Gmim Hosiana Tumatangtang Tomohon - Bobii, Elisabeth; Tuerah, Roos M.S.; Manopo, Seidi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The GMIM Hosiana Tumatangga Tomoho Kindergarten study used PTK examining group B samples. At GMIM Hosiana Tumatangga Tomoho Kindergarten, data collection techniques were applied through observation, question and answer, discussion and documentation using descriptive analysis techniques. Analysis of technical data looking at all aspects of the research activity during the research and analysis accordingly. The research results showed that the children's and oral language skills increased from the initial conditions in 2 children in the first period (25%) and in the second period with the method of storytelling through audiovisual media. the second reached 6 children (100%). Thus, it can be concluded that children and language skills can be improved through GMIM Hosiana Tumatantang Tomoho Kindergarten Group B narrative method using audio-visual media.